RESEARCH ON AXIAL MODIFICATION OF CROWD REDUCER GEARS OF LARGE MINING ELECTRIC EXCAVATOR - ZHANG YingHui; HOU Geng; HE WeiDong; ZHOU Feng; RU XueBin (Jixie qiangdu)
The crowd reducer gears of large mining electric excavator are low speed,heavy-duty and hard surface gears.In the mining process, the phenomenon of gear unbalanced load is inevitable.Through the modification of gears,it is possible to improve its carrying capacity and contact state. Using the thin slice gear model,statistical average load of excavator mining process is taken as the reference load of modification,the minimum contact stress of gears at the excavator mining position withmaximum statisticalcrowd force is regarded as the objective,the slope modification of the two stage pinion（driving wheel） of the crowd reducer is carried out.Further, no edge load at tooth surface in each mining location is regarded as the objective,the crown modification of the two stage pinion of the crowd reducer is carried out.In the process of excavator mining,compare with pinion without modification,the maximum stress（including contact stress of tooth surface and bending stress of tooth root）of thepinionwith modification decreases significantly,and the edge contact condition of tooth surface is obviously improved.After modification,when the gear is subjected to the statistical maximum load of excavator mining process,the stress value of the gearis still less than the allowable stress.Simulation results show that,axial modification of crowd reducer gears of large mining electric excavator has positive significance for improving carrying ability and contact condition of gears.